SOAL JAWAB remeh-temeh tentang TAHARAH [BERSUCI] tapi anda malu bertanya - Mohd. Azrul Azlen Abd. Hamid , author; Azhar Mohamed , author (Kuala Lumpur : Telaga Biru, 2008)
Includes bibliographical and references